School District Reform in Newark: Within- and Between-School Changes in Achievement Growth. (March 2019) - Chin, Mark; Kane, Thomas J.; Kozakowski, Whitney; Schueler, Beth E.; Staiger, Douglas O.
In the 2011–12 school year, the Newark Public School district (NPS) launched a set of educational reforms supported by a gift from Facebook CEO Mark Zuckerberg and Priscilla Chan. Using data from 2008–09 through 2015–16, the authors evaluate the change in Newark students' achievement growth relative to similar students and schools elsewhere in New Jersey. They measure achievement growth using a "value-added" model, controlling for prior achievement, demographics, and peer characteristics. By the fifth year of reform, Newark saw statistically significant gains in English language arts (ELA) achievement growth and no significant change in math achievement growth. Perhaps because of the disruptive nature of the reforms, growth declined initially before rebounding in later years. Much of the improvement was attributed to shifting enrollment from lower- to higher-growth district and charter schools.